Use of antiepileptic drugs in children with brain tumors: A review for acute management (2018)
Patients with primary or secondary tumors in the central nervous system may have seizures resulting from direct tissue damage, metabolic abnormalities, infection, or toxic side effects of medications. In pediatric patients, it is more frequent to use drugs to control secondary epilepsy. In this article, we discuss the main nuances of antiepileptic drugs for the proper management of children with central nervous system tumors.